A social innovation model for sustainable development: A case study of a Malaysian entrepreneur cooperative (KOKULAC) - Erne Suzila Kassim; Norol Hamiza Zamzuri; Siti Ayu Jalil; Sharmila Mohamed Salleh; Azhar Mohamad; Ramita Abdul Rahim (Administrative Sciences, 2022)
In Malaysia, social innovation programs are fully supported by the government. However, reports and findings on the related matter have yet to be comprehensively collected due to the current interest. Therefore, the aim of this paper was to provide a better insight and understanding on how social innovation projects could assist in achieving the SDG agenda. Since social innovation is emerging and has just recently been embraced in Malaysia, we present the study as a case based on an entrepreneur cooperative, named KOKULAC, with a grounded theory analysis as a core approach. The findings suggest that there are five sustainability development goals that are very closely related to KOKULAC's agenda. These goals are no poverty, zero hunger, decent work and economic growth, responsible consumption and production, and partnership for the goals. In addition, the case also presented how the values of sustainable development spur greater social benefits of shared prosperity. We conclude that the proposed model contributes to the expansion of innovation capability theory by shaping the innovations within the scope of social needs, which could be applied in other settings. For future research, we recommend a higher integration between the social innovation model and dynamic capabilities of the networking structures.
Keywords: 350; innovation capability; grassroots innovation; social innovation and shared prosperity; social innovation and sustainable development; social innovation in Malaysia; United Nations' Sustainable Development Goals